I Improving Students' Vocabulary Mastery Through Popular Songs (A Classroom Action Research In Sdn 2 Teloyo Wonosari) - Wahyuni., Sri (2012)
The objective of the research is to examine whether or not popular song can improve the students' vocabulary mastery. Besides that, the research is also want to know the effectiveness of the students' learning, the students' participation after conducting that popular songs in teaching learning process, and the strengths and weaknesses of popular song.. The research was carried out at SDN 2 Teloyo Wonosari, from June 2009 to September 2010. The subjects of the research are twenty six students of the third grade at SDN 2 Teloyo. Based on the problem statements, the research method is classroom action research conducted in three cycles. The data are collected quantitatively and qualitatively. To collect the quantitative data, the researcher used the students' pretest and posttest. To collect the qualitative data, the researcher conducted the direct observation interviews. Constant comparative Method designed by Strauss and Glasser is used to analyze the qualitative data. The research findings are described in line with the problem statements as follows: first, popular song can improve the student's vocabulary construction. Their memorizing are better than before, especially in remembering the word, and the written. The second, the popular song can improve the effectiveness of the students' learning. The students' score can pass the minimal standard score. The third, the popular song can improve the students' participation. It means that popular song give the students' interesting impression of learning, improve the students' motivation to study, and improve the students' interaction. The last, there are some strengths of popular song in teaching vocabulary. They were song is able to increase the student memory;to stimulate the student in inquiring the vocabulary construction; to improve the interactive learning in the classroom, to create the teaching learning process fun and enjoyable, and to reinforce the teaching point and saving the teacher unnecessary explanation. The research findings of this study imply that popular songs are very important to the vocabulary learning. Therefore, it is recommended that (1) the teacher should use the song in teaching learning process and decide the material sources that appropriate to the subject selectively. (2) The school institution facilitates the media such as the tape recorder as the main iand the casette as the instruments of teaching.